EVALUASI FUNGSI AUDITOR INTERNAL DALAM PENDETEKSIAN DAN PENCEGAHAN FRAUD PADA PDAM AIRMADIDI - Pua, Brenda Yusensie; Sondakh, Jullie J.; Pangerapan, Sonny (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Internal auditors have an important role in the company such as can provide suggestions for improvement within the company to avoid fraud that can lead to losses in the company. This study aims to determine whether the internal auditors in PDAM Airmadidi already run functions well and have been able to detect and prevent fraud in the company. The method used in this research is descriptive by describing the function of internal auditor through job description and internal auditor program in detecting and preventing fraud. The result of the research revealed that internal auditor function in detecting and preventing fraud in PDAM Airmadidi that internal auditor has performed function well can be seen from the duty of internal auditor: conduct examination either routine audit or special audit in which there is assessment on control system, supervision, inspection and provide suggestions for improvement within the company. The importance of management awareness of the internal control system within the company can also help to minimize the occurrence of fraud.Keywords: Internal Auditor, Fraud, Internal Control System